Transparent Things : The artist's use of the photograph. Works from the Canada Council Art Bank. - James, Geoffrey; Canada Council (Ottawa : Canada Council Art Bank, 1977)
Ayot, Pierre ; Béland, Luc ; Boogaerts, Pierre ; Bozak, Bob ; Carr-Harris, Ian ; Deitcher-Kropsky, Gloria ; Dickson, Jennifer ; Fones, Robert ; Gagnon, Charles ; General Idea ; Gledhill, Randy ; Goodwin, Betty ; Greer, John ; etc.
Transparent Things : The artist's use of the photograph. Works from the Canada Council Art Bank / Transparences : L'utilisation de la photographie par l'artiste. A partir de la Banque d'oeuvres d'art du Conseil des Arts du Canada, exposition, Ottawa, 1977
Engels & Frans
boek